2016
DOI: 10.1093/chromsci/bmw184
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Determination of Phenolics in Lamiaceae Species by UPLC-DAD-ESI-MS/MS

Abstract: This study reports the phenolic profile screening of aromatic Lamiaceae species such as marjoram (Origanum majorana L.), lavender (Lavandula officinalis) and pennyroyal (Mentha pulegium L.) using a novel and validated ultra performance liquid chromatography method coupled with DAD diode array detector and tandem mass spectrometry (MS/MS) in negative mode of electrospray ionization. Identification and quantification of phenolics in these plant extracts has been realized within 12 min. This method showed good pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…Another widely studied oregano species regarding antioxidant capacity is Origanum majorana , characterized by the high content of rosmarinic acid. The antioxidant capacity of the microwave assisted methanolic extract from the aerial parts of O. majorana was analyzed by the CUPRAC, DPPH and TPC methods, showing high values attributed to the elevated content of rosmarinic acid, along with apigenin, caffeic acid and rutin [ 75 ]. Similarly, Elansary and Mahmoud [ 76 ] reported that rosmarinic acid and caffeic acid were the main compounds on the infusion and methanolic extract of the leaves from Origanum majorana , were the last one showed better antioxidant capacity by DPPH, β-carotene bleaching and TPC.…”
Section: Health Benefits Of Flavonoids and Phenolic Compounds Frommentioning
confidence: 99%
“…Another widely studied oregano species regarding antioxidant capacity is Origanum majorana , characterized by the high content of rosmarinic acid. The antioxidant capacity of the microwave assisted methanolic extract from the aerial parts of O. majorana was analyzed by the CUPRAC, DPPH and TPC methods, showing high values attributed to the elevated content of rosmarinic acid, along with apigenin, caffeic acid and rutin [ 75 ]. Similarly, Elansary and Mahmoud [ 76 ] reported that rosmarinic acid and caffeic acid were the main compounds on the infusion and methanolic extract of the leaves from Origanum majorana , were the last one showed better antioxidant capacity by DPPH, β-carotene bleaching and TPC.…”
Section: Health Benefits Of Flavonoids and Phenolic Compounds Frommentioning
confidence: 99%
“…However, luteolin-7- O -glucuronide was also detected in high quantities for the first time in thyme ( Thymus ) species ( Table S1 ), whereas other novel compounds were also present ( Table S1 ) [ 59 ]. Several studies have demonstrated the application of UHPLC-MS/MS for phenolic profiling of herbal samples [ 55 , 64 , 66 , 68 ] which is deliberated as advanced, sensitive, reproducible, rapid and with high resolution technique [ 68 ]. For instance, Mena et al [ 53 ] have used UHPLC-ESI-MS n with a total run time of 35 min, for the phenolic compositional analysis of a branded extract of Rosmarinus officinalis ( Table 2 ), where 57 compounds were identified and quantified, and of which 14 polyphenols were detected for the first time ( Table S1 ) in this species [ 53 ].…”
Section: Hyphenated Chromatographic Techniquesmentioning
confidence: 99%
“…The benefits of these techniques stem from the used analytical columns, with particle size <2.0 μm, which lead to considerable reduction of back-pressure [ 14 ]. Polyphenolic profiles of Lamiaceae species, namely Origanum majorana , Mentha pulegium and lavender ( Lavandula officinalis ) were also scrutinised by Çelik et al [ 68 ] on MAE 60% MeOH extracts ( Table 2 ). The authors optimized and validated the UHPLC-DAD-ESI-MS/MS method that had a total run time of 12 min per sample.…”
Section: Hyphenated Chromatographic Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…The chromatographic analysis of antioxidant compounds in marigold extracts was performed by UPLC-PDA-ESI-MS/MS system (Waters) as described by Çelik et al [27]; 0.1% HCOOH in bidistilled H 2 O (A) and 0.1%…”
Section: Chromatographic Analysis Of Antioxidant Compounds In Marigolmentioning
confidence: 99%